Sisters - Telgemeier, Raina; Telgemeier, Raina (New York, NY : Graphix, an imprint of Scholastic, 2014)
In graphic novel format, Raina Telgemeier shares the story of her relationship with her younger sister.
Companion to: Smile.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, June 2014
Kirkus Starred, June 2014
Keywords: Brothers and sisters -- Comic books, strips, etc -- Juvenile literature; Families -- Comic books, strips, etc -- Juvenile literature; Interpersonal relations -- Comic books, strips, etc -- Juvenile literature; Brothers and sisters -- Cartoons and comics; Cartoons and comics; Family life -- Cartoons and comics; Interpersonal relations -- Cartoons and comics; Comic books, strips, etc; Family life -- Comic books, strips, etc; Interpersonal relations -- Comic books, strips, etc; Siblings -- Comic books, strips, etc